2014
DOI: 10.1177/2158244014554961
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Human Papilloma Virus Vaccination and Pap Smear Screening Intentions Among Young Singaporean Women Using the Theory of Planned Behavior

Abstract: We used the Theory of Planned Behavior (TPB) to analyze the role of attitudes, subjective norms, and perceived behavioral control as predictors of intentions to obtain Human Papillomavirus (HPV) vaccinations or a Papanicolaou (Pap) smear in a sample of young Singaporean women. A further aim was to evaluate knowledge of cervical cancer and preventive measures as a possible additional predictor of intentions. A purpose-designed TPB and knowledge questionnaire was completed by 206 women aged 18 to 26 years living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
5
10
1
Order By: Relevance
“…Out of the 3 components of the TPB, social norms and PBC were signi cant in determining the intention to socially distance, while attitude was not a signi cant predictor of intention. These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor.…”
Section: Discussionsupporting
confidence: 92%
“…Out of the 3 components of the TPB, social norms and PBC were signi cant in determining the intention to socially distance, while attitude was not a signi cant predictor of intention. These ndings are in agreement with a previous study that found subjective norms and PBC had a signi cant impact on behavioral intentions [44]; [45]; [46]. In line with the ndings of Alfahan's study [47], the social norm component emerged as the most important predictor.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the rate is slightly higher than reported among young women in Hong Kong (9.7%), in 2008, when the vaccines were newly introduced to the country [23]. The HPV vaccine uptake rate has remained low in other countries in Asia, such as Singapore where only 13.6% women aged 18 to 26 years reported having been immunized against HPV [24]. In this study, based on the results of the PLS-SEM, indicators of higher socioeconomic status such as residing in the eastern region, being born in a city area, and a higher monthly disposable fund were found to correlate with the HPV vaccine uptake.…”
Section: Discussionmentioning
confidence: 93%
“…The vaccination is currently covered under the Medisave programme but relies on voluntary initiation or parental initiation, which may explain the current low uptake rate (13.6%). (18) Official recommendation from relevant medical societies, endorsement of the AS04-HPV-16/18v from MOH Singapore and Health Promotion…”
Section: Discussionmentioning
confidence: 99%
“…(17) So far, the uptake of HPV vaccination has also been low; only 13.6% of women aged 18-26 years have been immunised. (18) The reasons contributing to the low uptake are unclear, but inconvenience, low awareness of HPV and the benefits of HPV vaccination, along with misconceptions about the safety of HPV vaccination have been raised as potential barriers to uptake. (14,19) A recent meta-analysis concluded that AS04-HPV-16/18v was more efficacious compared with 4vHPV in terms of protection against the pre-malignant stages CIN2 (65% vs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation